A new species of Heterochondria (Copepoda: Chondracanthidae) parasitic on many-banded sole, Zebrias fasciatus (Pleuronectiformes: Soleidae) from Korea, with a key to the species of the genus - Moon, Seong Yong; Soh, Ho Young (Folia parasitologica, 2013)
A new species of Chondracanthidae (Copepoda: Cyclopoida), Heterochondria orientalis sp. n., is described based on specimens of both sexes collected from the gill rakers and the inner side of the operculum of the many-banded sole, Zebrias fasciatus (Basilewsky), from the Yellow Sea, Korea. The new species resembles most closely H. zebriae (Ho, Kim et Kuman, 2000), but can be distinguished from this species and other congeners by the shape of the trunk and length of the antenna, the number of teeth on the mandible and the terminal process of the maxilla, and the structure of the male antennule and maxilliped. Heterochondria orientalis is the first copepod species reported from Z. fasciatus and the first heterochondrid species reported from sole fishes in the Northwest Pacific. A key to distinguish all 10 nominal species of the genus is provided.
Keywords: Parasitic Diseases, Animal; Republic of Korea; Female; Flatfishes; Copepoda; nemoci ryb; Animals; ženské pohlaví; mužské pohlaví; Male; parazitární nemoci u zvířat; zvířata; platýsi; Fish Diseases; Korejská republika